Anxiety in English speaking classes experienced by English majored freshmen at a teacher training college in Vietnam = sự lo lắng trong giờ học kỹ năng nói của sinh viên năm thứ nhất chuyên ngành tiếng Anh tại một trường cao đẳng sư phạm ở Việt - Nguyễn, Thị Châm (2019)
The present study aimed to investigate anxiety in English speaking classes experienced by English majored freshmen at a teacher training college in Viet Nam. This study used a mixed methods design to achieve its research aims. In the quantitative phase, a questionnaire was administered to a group of 46 first year English major students at the teacher training college.